Increased nitrous oxide emissions from intertidal soil receiving wastewater from dredging shrimp pond sediments. (18th August 2020) - Chen, Guangcheng; Chen, Jiahui; Ou, Danyun; Tam, Nora F Y; Chen, Shunyang; Zhang, Qinghua; Chen, Bin; Ye, Yong
Abstract: The quantities of greenhouse gas emissions and the activity of functional microbes in coastal soils receiving nutrient-rich wastewaters from mariculture activities have seldom been reported. We investigated the effects of wastewater discharge resulting from dredging shrimp pond sediment on the soil fluxes of methane (CH4 ) and nitrous oxide (N2 O) in intertidal areas and on the functional microorganisms and physio-chemical characteristics of soil. The temporal variations in gas fluxes and soil characteristics following wastewater discharge were also evaluated with the tidal regime on the day of discharge taken into account. The results showed that wastewater discharge immediately resulted in higher levels of ammonia (NH4 + -N) deposited and N2 O emissions from the soil at the discharge site than at the non-discharge site, while the CH4 flux was not affected. The increase in N2 O flux lasted for a longer time when the discharge was performed during a neap tide day than when it was performed during a spring tide day. Wastewater discharge also increased the abundance of ammonia-oxidizing bacterial (AOB) amoA genes and nosZ genes in soil rather than increasing the abundance of narG and nirK genes. The pattern of temporal variations between the N2 O flux and soil NH4 + –N content was similar to that between the flux and the AOB- amoA gene abundance, suggesting that bacterial nitrification was important for N2 O production in soil receiving the dredging wastewater. The results suggest that the wastewater discharge impacts nitrogen metabolism processes and causes a significant N2 O emission problem; therefore, pollutant management is essential in shrimp culturing activities to reduce greenhouse gas emissions into the atmosphere.